Mathematical models for evaluating efficiency and quality of means for synchronization of interacting processes in reconfigurable computer systems - Martyshkin, Alexey (Revista de la Universidad del Zulia, 2019)
In this paper, the modelling method is applied to evaluate the performance characteristics of various methods for synchronization of parallel processes in order to determine which way to use to implement them: software or hardware. Comparative characteristics of process synchronization by the spin lock method and the core lock method are presented. Charts have been constructed that display the obtained characteristics.